A Nuclear Twin Family Study of Self‐Esteem. Issue 3 (17th January 2018) - Bleidorn, Wiebke; Hufer, Anke; Kandler, Christian; Hopwood, Christopher J.; Riemann, Rainer
Abstract: Twin studies suggest that both genes and environments influence the emergence and development of individual differences in self‐esteem. However, different lines of research have emphasized either the role of genes or of environmental influences in shaping self‐esteem, and the pathways through which genes and environments exert their influence on self‐esteem remain largely unclear. In this study, we used nationally representative data from over 2000 German twin families and a nuclear twin family design (NTFD) to further our understanding of the genetic and environmental influences on individual differences in self‐esteem. Compared with classical twin designs, NTFDs allow for finer‐grained descriptions of the genetic and environmental influences on phenotypic variation, produce less biased estimates of those effects, and provide more information about different environmental influences and gene–environment correlation that contribute to siblings' similarity. Our NTFD results suggested that additive and non‐additive genetic influences contributed to individual differences in self‐esteem as well as environmental influences that are both shared and not shared by twins. The shared environmental component mostly reflected non‐parental influences. These findings highlight the increased sensitivity afforded by NTFDs but also remaining limitations that need to be addressed by future behavioural genetic work on the sources of self‐esteem. Copyright © 2018 European Association of Personality Psychology